2001
DOI: 10.1039/b104671n
|View full text |Cite
|
Sign up to set email alerts
|

Conformational isomerism in methyl cyanoacetate: A combined matrix-isolation infrared spectroscopy and molecular orbital study

Abstract: Study of the conformational isomerism of methyl cyanoacetate MCA) aided for the Ðrst (N3CCH 2 COOCH 3 , time by matrix-isolation infrared spectroscopy is reported. The conformational isomerization processes in MCA in the temperature range from 10 to 70 K were studied in detail in argon and xenon matrixes. During annealing of the matrixes direct interconversion of the gauche into the syn conformer has been registered. A similar, but more pronounced, gauche ] syn interconversion e †ect was observed in a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 22 publications
6
43
0
Order By: Relevance
“…The local order is also higher in the case of the matrix experiment, as they are the packing requirements, since the arriving molecule faces an essentially crystalline media (argon crystal), while in the case of deposition of the amorphous layer it faces an essentially disordered molecular environment. It is well known that in general more planar structures are stabilized in matrices [43,44]. On the other hand, the local electric field is considerably more important for the amorphous layer.…”
Section: Resultsmentioning
confidence: 99%
“…The local order is also higher in the case of the matrix experiment, as they are the packing requirements, since the arriving molecule faces an essentially crystalline media (argon crystal), while in the case of deposition of the amorphous layer it faces an essentially disordered molecular environment. It is well known that in general more planar structures are stabilized in matrices [43,44]. On the other hand, the local electric field is considerably more important for the amorphous layer.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, with such a low energy barrier for Z f E conversion, the residual amount of Z molecules existing in the gas phase prior to deposition can be expected to rapidly convert to the most stable form during deposition of the matrix. [43][44][45][46][47] Because of the excellent agreement between the theoretical and experimental spectra (Figure 5), the general assignment of the experimental bands was straightforward (Table 2). Interestingly, the detailed analysis of the experimental spectra revealed that PZA molecules occupy three main matrix sites in the argon matrix, with most of the bands appearing split into triplets.…”
Section: Resultsmentioning
confidence: 99%
“…Another compound undergoing conformational cooling in matrixes is methyl cyanoacetate (MCA), which we have recently studied [7]. According to the MP2/6-31G** calculations, in the gaseous phase this molecule has two almost isoenergetic conformers differing in the relative orientation of the cyano and methylcarboxyl groups.…”
Section: Introductionmentioning
confidence: 99%